Aplikasi Pemesanan Wedding Organizer Deccoration Berbasis Web Menggunakan Metode Analytical Hierarchy Procsess (AHP) Studi Kasus Banjarnegara Komunitas Dekor - Sofiatul Musarofah; Muh. Zia Ulkhaq; Ida Cahyani (Journal Of Informatics And Busisnes, 2025)
The development of digital technology has driven significant changes in various fields, including wedding organizer decoration services. In Banjarnegara, decoration communities still use manual booking systems through social media, which leads to inefficiencies, lack of data integration, and difficulties for customers in selecting the most suitable decoration. Based on these problems, this study aims to develop a web-based wedding organizer decoration booking application by applying the Analytical Hierarchy Process (AHP) method to provide the best decoration recommendations for customers. The research method used is the waterfall system development model, consisting of requirements analysis, design, implementation, and testing stages. Data were collected through interviews with business practitioners and questionnaires distributed to users, while evaluation was carried out using the Likert scale. The system was developed using the PHP programming language and MySQL database, and is equipped with features for booking, vendor management, and AHP-based recommendations with criteria such as price, quality, reviews, and popularity. The results show that the application was successfully developed and functions according to requirements. Based on black box testing, all features worked properly. Meanwhile, the user evaluation through questionnaires obtained an acceptance rate of 87.63% in the “Excellent” category. Thus, this application can help improve efficiency, transparency, and customer satisfaction in selecting wedding decoration services.